REHABILITASI PENGHUNI RUMAH TAHANAN SURAKARTA MELALUI PENDIDIKAN AGAMA - Fauzi Muharom (State Institute of Islamic Studies (IAIN) Salatiga, 2012)
This study is focused to know the implementation of Islamic Education informally held for prisoners in Surakarta Jail. Though the prisoners are marginal society, mental and spiritual education is an important thing to do. The data gathered through interviews, observations and documentations. This study held during the Fasting Month (Ramadhan) which may particularly brings certain impressions on the results. The study found out that there were Islamic Education informally held forprisoners consisted of Learning Al-Qur’an, memorizing the whole verses of Al-Qur’an, advices after dzuhur prayer, advices after ashar prayer, Isya and Tarawih prayers held together, advices after Tarawih, Reading Al-Qur’an together. The supporting factors for this agenda were the good cooperation between the Surakarta Jail and other institutions. In the other hands, the drawbacks were the reluctant of prisoners in joining the agenda and the conflicting of the prisoners schedule.